Exchange transfusion of a patient with fulminant Lassa fever. Issue 784 (February 1991) - Cummins, D.; Bennett, D.; Machin, S. J.
Abstract : We report a patient with fulminant Lassa fever who responded dramatically to a 2.5-litre exchange transfusion of whole blood. On admission he was semicomatose with facial oedema and oral haemorrhage; his platelets showed markedly depressed aggregation to ADP; and his plasma inhibited the aggregation responses of normal platelets in vitro. Exchange transfusion resulted in rapid clinical improvement, recovery of platelet function, and disappearance of platelet-inhibitory activity in plasma. The patient died 2 weeks later from an acute encephalopathy. His initial response was sufficiently impressive to suggest that further evaluation of this therapeutic approach is justified in selected patients with overwhelming Lassa virus infection.